The animated man a life of Walt Disney - Barrier, J. Michael (Univ. of California Press, 2007)
"Walt Disney (1901-1966) was one of the most significant creative forces of the twentieth century, a man who made a lasting impact on the art of the animated film, the history of American business, and the evolution of twentieth-century American culture. He was both a creative visionary and a dynamic entrepreneur, roles whose demands he often could not reconcile. In his compelling new biography, noted animation historian Michael Barrier avoids the well-traveled paths of previous biographers, who have tended to portray a blemish-free Disney or to indulge in lurid speculation. Instead, he takes the full measure of the man in his many aspects. A consummate storyteller, Barrier describes how Disney transformed himself from Midwestern farm boy to scrambling young businessman to pioneering artist and, finally, to entrepreneur on a grand scale. Barrier describes in absorbing detail how Disney synchronized sound with animation in Steamboat Willie; created in Snow White and the Seven Dwarfs sympathetic cartoon characters whose appeal rivaled that of the best live-action performers; grasped television's true potential as an unparalleled promotional device; and-not least-parlayed a backyard railroad into the Disneyland juggernaut." -- Publisher's description.